PENGEMBANGAN UMKM TAHU YANG DI OLAH MENJADI SEMPOL GUNA MENINGKATKAN EKONOMI MASYARAKAT DESA BANJAR NEGERI - SUSANTI, AGUS; AGUSTIN, ULLY; AKBAR, MUHAMMAD SULTHAN; LATIFAH, TATIK; RAMADHANI, SYAHRURROFI (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in rural Indonesia's economy. This study focuses on developing MSMEs in Banjar Negeri Village through the innovation of processing tofu into sempol. The main objectives of the program are to enhance product quality, production capacity, and market competitiveness of MSMEs. The methodology includes problem identification, program planning, training and workshop implementation, and monitoring and evaluation. The results show that training and modern equipment have successfully improved the quality of sempol, increased production volume, and expanded market reach. The enhancement in quality and marketing strategies also positively affected MSME revenues, subsequently improving the welfare of the village community. The program demonstrates that technology support, training, and effective marketing strategies are key to driving rural economic growth and improving community living standards. ABSTRAKUMKM memiliki peran penting dalam ekonomi pedesaan Indonesia. Penelitian ini fokus pada pengembangan UMKM di Desa Banjar Negeri dengan inovasi pengolahan tahu menjadi sempol. Program ini bertujuan meningkatkan kualitas produk, kapasitas produksi, dan daya saing UMKM. Metodologi mencakup identifikasi masalah, perencanaan, pelatihan, dan evaluasi. Hasil menunjukkan bahwa pelatihan dan peralatan modern meningkatkan kualitas sempol, volume produksi, dan pasar. Peningkatan kualitas dan strategi pemasaran juga berdampak positif pada pendapatan UMKM, yang meningkatkan kesejahteraan masyarakat desa. Program ini membuktikan bahwa teknologi, pelatihan, dan pemasaran efektif dalam memajukan ekonomi pedesaan dan kualitas hidup masyarakat.